Å flette og veve med samiske kunnskapsforståelser i barnehagen - Myrstad, Anne (Speki. Nordic Philosophy and Education Review, 2024)
Making space for Sámi knowledge in kindergarten is the focus of the article. Making space refers concretely to the design of a Sámi-inspired outdoor area in an urban kindergarten, located in Sápmi. In the kindergarten's outdoor area, two play installations have been designed with clear references to Sea Sámi coastal culture. By applying relational Sámi approaches to knowledge, the article highlights how the installations are more than an innovative backdrop for children's play and activity. In such a perspective, the installations can be regarded as entrances to Sámi understanding of knowledge, where material culture is regarded as relational ties between people and the environment. Thinking with a braiding metaphor, rooted in indigenous epistemology, the article will discuss how Sámi knowledge can be understood and emphasized in the education system, in which kindergarten is a part of.